2023
DOI: 10.1093/bjs/znad105
|View full text |Cite
|
Sign up to set email alerts
|

European e-Delphi process to define expert consensus on electrochemotherapy treatment indications, procedural aspects, and quality indicators in melanoma

Abstract: Background Skin metastases are an important co-morbidity in melanoma. Despite broad adoption, electrochemotherapy implementation is hindered by a lack of treatment indications, uncertainty regarding procedural aspects, and the absence of quality indicators. An expert consensus may harmonize the approach among centres and facilitate comparison with other therapies. Methods An interdisciplinary panel was recruited for a three-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Despite the development of electric protocols and the availability of standard operating procedures for some PEF-based therapies (e.g., the ESOPE guidelines [ 150 ]), some variation remains across centres in treatment delivery. For instance, bleomycin dose and electrode application (i.e., the inclusion of a safety margin) is a matter of debate among ECT users [ 268 ], whereas the standardisation of energy delivery is a controversial aspect in IRE [ 267 ]. At the same time, improving treatment precision, particularly for deep-seated lesions, can potentially ensure patient safety and improve treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the development of electric protocols and the availability of standard operating procedures for some PEF-based therapies (e.g., the ESOPE guidelines [ 150 ]), some variation remains across centres in treatment delivery. For instance, bleomycin dose and electrode application (i.e., the inclusion of a safety margin) is a matter of debate among ECT users [ 268 ], whereas the standardisation of energy delivery is a controversial aspect in IRE [ 267 ]. At the same time, improving treatment precision, particularly for deep-seated lesions, can potentially ensure patient safety and improve treatment results.…”
Section: Discussionmentioning
confidence: 99%
“…Both these drugs represent the best choices for ECT, since they both disperse scantily throughout the cell membrane and are highly cytotoxic inside cells [93]. ECT was first approved for head and neck squamous cell carcinomas following a clinical trial in 1993, but nowadays, it finds its main applications in melanoma and Kaposi sarcoma [94,95]. Kunte et al, demonstrated that, in 151 patients with metastatic melanoma, among the 394 lesions treated, 306 (78%) showed OR, while 229 (58%) showed a complete response [96].…”
Section: Electrochemotherapymentioning
confidence: 99%
“…Kunte et al, demonstrated that, in 151 patients with metastatic melanoma, among the 394 lesions treated, 306 (78%) showed OR, while 229 (58%) showed a complete response [96]. According to the European expert consensus, the ideal patient with in-transit melanoma metastases that could benefit from ECT should have fewer than 10 tumors smaller than 3 cm, or fewer than 20 smaller than 1 cm, and they should involve the same limb segment over an area not exceeding 10 cm [94]. ECT can induce immunogenic cell death (ICD), stimulating the immune system, mainly dendritic cells (DCs) and macrophages, through damageassociated molecular patterns (DAMPs) such as calreticulin (CRT), heat shock proteins, high-mobility group box 1 (HMGB1), type I IFN, and ATP [97,98].…”
Section: Electrochemotherapymentioning
confidence: 99%